Oxidative Stress Markers and Modified Model for End-Stage Liver Disease Are Associated with Outcomes in Patients with Advanced Heart Failure Receiving Bridged Therapy with Continuous-Flow Left Ventricular Assist Devices - Bożena Szyguła-Jurkiewicz; Wioletta Szczurek-Wasilewicz; Mariusz Gąsior; Izabela Copik; Justyna Małyszek-Tumidajewicz; Michał Skrzypek; Ewa Romuk; Michał Zembala; Marian Zembala; Piotr Przybyłowski (MDPI AG, 2021)
Left ventricular assist device (LVAD) is well established as an alternative treatment for end-stage heart failure (HF) patients. The aim of the study was to determine the prognostic value of oxidative stress markers and the modified Model for End-Stage Liver Disease (modMELD) in patients receiving bridged therapy with continuous-flow LVAD. We prospectively analyzed 36 end-stage HF patients who received LVAD therapy between 2015 and 2018. The total antioxidant capacity (TAC) and total oxidant status (TOS) were measured by the methods described by Erel. The oxidative stress index (OSI) was defined as the ratio of the TOS to TAC levels. The modMELD scores were calculated based on the serum bilirubin, creatinine, and albumin levels. The patients' median age was 58 (50-63.0) years. During the 1.5-years follow-up, a major adverse cardiac event-MACE (death, stroke, or pump thrombosis) was observed in 17 patients (47.2%). The area under the receiver operating characteristics curves (AUCs) indicated a good prognostic power of TAC (AUC 0.7183 (0.5417-0.8948)), TOS (AUC 0.9149 (0.8205-0.9298)), OSI (AUC 0.9628 (0.9030-0.9821)), and modMELD (AUC 0.87 (0.7494-0.9905)) to predict a MACE. Oxidative stress markers serum concentrations, as well as the modMELD score, allow the identification of patients with a risk of MACE.